Nuclear localization of suppressor of cytokine signaling-1 regulates local immunity in the lung - Zimmer, Jana; Weitnauer, Michael; Boutin, Sébastien; Küblbeck, Günter; Thiele, Sabrina; Walker, Patrick; Lasitschka, Felix; Lunding, Lars; Orinska, Zane; Vock, Christina; Arnold, Bernd; Wegmann, Michael; et al. (Frontiers in immunology, 2016)
Suppressor of cytokine signaling 1 (SOCS1) is a negative feedback inhibitor of cytoplasmic Janus kinase and signal transducer and activator of transcription (STAT) signaling. SOCS1 also contains a nuclear localization sequence (NLS), yet, the in vivo importance of nuclear translocation is unknown. We generated transgenic mice containing mutated Socs1ΔNLS that fails to translocate in the cell nucleus (MGLtg mice). Whereas mice fully deficient for SOCS1 die within the first 3 weeks due to excessive interferon signaling and multiorgan inflammation, mice expressing only non-nuclear Socs1ΔNLS (Socs1−/−MGLtg mice) were rescued from early lethality. Canonical interferon gamma signaling was still functional in Socs1−/−MGLtg mice as shown by unaltered tyrosine phosphorylation of STAT1 and whole genome expression analysis. However, a subset of NFκB inducible genes was dysregulated. Socs1−/−MGLtg mice spontaneously developed low-grade inflammation in the lung and had elevated Th2-type cytokines. Upon ovalbumin sensitization and challenge, airway eosinophilia was increased in Socs1−/−MGLtg mice. Decreased transepithelial electrical resistance in trachea epithelial cells from Socs1−/−MGLtg mice suggests disrupted epithelial cell barrier. The results indicate that nuclear SOCS1 is a regulator of local immunity in the lung and unravel a so far unrecognized function for SOCS1 in the cell nucleus.
Gesehen am 08.10.2021